Погрешности при измерении характеристик рентгеновских установок - Dushkin, S. A.; Ivanskiy, V. B.; Kurov, A. M.; Odinets, V. A.; Orobinskiy, A. N. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
Expressions for calculating the measurement errors of X-ray devices features are given as follows: mean photon energy, homogeneity coefficient, the first and the second half-value layer (1st HVL, 2nd HVL). Comparison of errors is organized at measurement and calculation of features of X-ray installation with requirements to errors of standard X-ray radiation features with narrow spectrum on DSTU ISO 4037-1:2006. Criteria of choosing the additional filters thickness for measurement 1st HVL and 2nd HVL are defined. The errors resulting from calculation of mean photon energy of X-ray radiation and homogeneity coefficient are specified.